Razonamiento jurídico: Lógica, interpretación y argumentación - Lagla Pillajo, Mabell Abigail (2018)
RESUMENEl presente trabajo investigará los aspectos más importantes de la lógica de lo razonable, en el cual la argumentación juega un papel fundamental mientras que la interpretación jurídica, no se encuentra ajena a ello. Además, se recurrirá al razonamiento jurídico, el cual pretende como fin último la búsqueda de una solución ante el conflicto, por medio de la aplicación de una proposición normativa, que debe ser justificada y fundada como fruto de una decisión. ABSTRACTThe present work will investigate in the most important aspects of the logic of the reasonable, in which the argument plays a fundamental role and while the juridical interpretation, is not alien. Legal reasoning seeks as the ultimate goal the search for a solution to the conflict, through the application of a normative proposition, which must be justified and founded as the result of a decision. The importance that it has for the juridical world, we can discover with just thinking, in the procedural law that has at last to regulate the form of the dispute or judicial controversy, in which the parties are thrown in a discussion where they argue and debate, In order that an impartial third party of credit to its positions and fails as dictated by the right. KEYWORDS: Legal reasoning, normative proposal, legal interpretation, argumentation, motivation. JEL CODE / CLASIFICACIÓN JEL: A14, Y80